Clonal haematopoiesis of indeterminate potential predicts incident cardiac arrhythmias - Schuermans, Art; Vlasschaert, Caitlyn; Nauffal, Victor; Cho, So Mi Jemma; Uddin, Md Mesbah; Nakao, Tetsushi; Niroula, Abhishek; Klarqvist, Marcus D R; Weeks, Lachelle D; Lin, Amy E; Saadatagah, Seyedmohammad; Lannery, Kim; et al. (European heart journal, 2024)
Abstract Background and Aims Clonal haematopoiesis of indeterminate potential (CHIP), the age-related expansion of blood cells with preleukemic mutations, is associated with atherosclerotic cardiovascular disease and heart failure. This study aimed to test the association of CHIP with new-onset arrhythmias. Methods UK Biobank participants without prevalent arrhythmias were included. Co-primary study outcomes were supraventricular arrhythmias, bradyarrhythmias, and ventricular arrhythmias. Secondary outcomes were cardiac arrest, atrial fibrillation, and any arrhythmia. Associations of any CHIP [variant allele fraction (VAF) ≥ 2%], large CHIP (VAF ≥10%), and gene-specific CHIP subtypes with incident arrhythmias were evaluated using multivariable-adjusted Cox regression. Associations of CHIP with myocardial interstitial fibrosis [T1 measured using cardiac magnetic resonance (CMR)] were also tested. Results This study included 410 702 participants [CHIP: n = 13 892 (3.4%); large CHIP: n = 9191 (2.2%)]. Any and large CHIP were associated with multi-variable-adjusted hazard ratios of 1.11 [95% confidence interval (CI) 1.04–1.18; P = .001] and 1.13 (95% CI 1.05–1.22; P = .001) for supraventricular arrhythmias, 1.09 (95% CI 1.01–1.19; P = .031) and 1.13 (95% CI 1.03–1.25; P = .011) for bradyarrhythmias, and 1.16 (95% CI, 1.00–1.34; P = .049) and 1.22 (95% CI 1.03–1.45; P = .021) for ventricular arrhythmias, respectively. Associations were independent of coronary artery disease and heart failure. Associations were also heterogeneous across arrhythmia subtypes and strongest for cardiac arrest. Gene-specific analyses revealed an increased risk of arrhythmias across driver genes other than DNMT3A. Large CHIP was associated with 1.31-fold odds (95% CI 1.07–1.59; P = .009) of being in the top quintile of myocardial fibrosis by CMR. Conclusions CHIP may represent a novel risk factor for incident arrhythmias, indicating a potential target for modulation towards arrhythmia prevention and treatment. Structured Graphical Abstract Structured Graphical Abstract In 410 702 middle-aged adults from the UK Biobank, clonal haematopoiesis of indeterminate potential (CHIP) was associated with incident arrhythmias independent of other cardiovascular diseases such as coronary artery disease and heart failure, with the strongest associations observed for cardiac arrest. Gene-stratified analyses revealed an increased risk of arrhythmias across driver genes other than DNMT3A. CI, confidence interval; HR, hazard ratio.